The Effectiveness of E-Scrapbook Media Containing HOTS Questions on Science Learning Outcomes of Elementary School Students - Parmiti, Desak Putu; Antara, I Gede Wahyu Suwela; Wulandari, I Gusti Ayu Agung Manik (Journal of Education Reseach and Evaluation, 2022)
The low ability of Indonesian students is related to the science learning process which has not fully provided opportunities for students to develop critical reasoning skills. This study aims to analyze the effectiveness of the E-Scrapbook media containing HOTS questions on the learning outcomes of fourth grade elementary school students. This research is an experimental research using a quantitative approach. The research design used in this study was a one group pre-test post-test design. The subjects of this study amounted to 30 elementary school fourth grade students. The effectiveness of using E-Scrapbook media with HOTS questions can be measured using the test method. The data analysis method used in this research is descriptive and inferential analysis. The analytical technique used to test the hypothesis is Paired Sample T-Test. Hypothesis testing using the help of the IBM SPSS Statistics for Windows version 21.0 program. There is a significant difference in the learning outcomes of students' science before and after participating in learning using the E-Scrapbook media containing HOTS-Based Questions. Thus, the application of E-Scrapbook media containing HOTS-based questions in the learning process effectively has an influence in improving student learning outcomes.